2005
DOI: 10.1097/01.aog.0000171113.36624.86
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise and Submaximal Functional Capacity in Overweight Pregnant Women

Abstract: Aerobic training in overweight pregnant women substantially increases submaximal exercise capacity, overcoming the otherwise negative effects of pregnancy in this regard. Additional studies are required to evaluate its effect on major clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
196
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(201 citation statements)
references
References 15 publications
1
196
0
4
Order By: Relevance
“…Findings from intervention studies using only exercise were less consistent than findings from intervention studies combining exercise and nutrition. Seven trials reported a trend for less GWG in the exercise group (Barakat et al, 2009;Cavalcante et al, 2009;Clapp et al, 2000;Ong et al, 2009;Santos et al, 2005;Sedaghati et al, 2007;Yeo, 2009) which was significant in only one of these trials (Sedaghati et al, 2007). Five trials reported that women in the exercise group did not gain significantly less weight than women in the control group (Collings et al, 1983;Garshasbi & Faghih Zadeh, 2005;Hopkins et al, 2010;Marquez-Sterling et al, 2000;Prevedel et al, 2003).…”
Section: Maternal Physical Activity Is Associated With Preventing Excmentioning
confidence: 99%
“…Findings from intervention studies using only exercise were less consistent than findings from intervention studies combining exercise and nutrition. Seven trials reported a trend for less GWG in the exercise group (Barakat et al, 2009;Cavalcante et al, 2009;Clapp et al, 2000;Ong et al, 2009;Santos et al, 2005;Sedaghati et al, 2007;Yeo, 2009) which was significant in only one of these trials (Sedaghati et al, 2007). Five trials reported that women in the exercise group did not gain significantly less weight than women in the control group (Collings et al, 1983;Garshasbi & Faghih Zadeh, 2005;Hopkins et al, 2010;Marquez-Sterling et al, 2000;Prevedel et al, 2003).…”
Section: Maternal Physical Activity Is Associated With Preventing Excmentioning
confidence: 99%
“…Many women who are accustomed to regular exercise outside pregnancy, therefore, wish to continue exercising during pregnancy. In healthy pregnant women, regular aerobic exercise during pregnancy maintains or improves physical fitness with studies demonstrating improvements in functional aerobic capacity and cardiorespiratory capacity (25)(26)(27)(28) . Short bouts of maternal exercise are also associated with fetal physiological responses, in particular, an increase in fetal heart rate (29,30) .…”
Section: Exercisementioning
confidence: 99%
“…Studies recruiting women in high-risk groups: there were differences in the prepregnancy weight of women recruited to studies; only women who were overweight or obese were recruited in studies by Guelinckx 2010;Quinlivan 2011;Santos 2005;Thornton 2009;Wolff 2008; women who were either considered overweight or appeared to be gaining excessive weight in early pregnancy were recruited by Boileau 1968 andSilverman 1971. Women with or at high risk of gestational diabetes were included in four studies (Korpi-Hyovalti 2011;Luoto 2011;Moses 2009;Rae 2000) A mix of underweight, normal, overweight, and obese women were included in studies by Jeffries 2009;Phelan 2011;Polley 2002;Vitolo 2011 with separate results provided for women in the overweight/obese groups.…”
Section: Objectivesmentioning
confidence: 99%